CHOC'LATE: A Framework for Specificationbased Testing. - PAK-LOK POON; SAU-FUN TANG; TSE, T. H.; CHEN, T. Y. (Communications of the ACM, 2010)
The article discusses software testing based on informal specifications. The authors present a Choice Relation Framework (CHOC'LATE) which allows testers to reenact an unstructured informal specification in a more formal choice relation table from which a test suite, which is the set of test cases used, can be generated automatically. The difference between informal and formal specifications as it applies to generating a test suite is explored. The consistency checking, automatic deductions, and choice prioritization of CHOC'LATE are discussed.